Solutions by everydaycalculation.com

How to solve 6x + 9 = 3x + 6? Get the answer and stepwise instruction to solve linear equation in one variable 𝒙.

We have 6**x** + 9 = 3**x** + 6

First, we move the * x* terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.

Transposition is a faster method and combines the following two steps, were we to solve the equation by:

i) Subtracting 9 from both sides

ii) Subtracting 3**x** from both sides

Therefore, 6**x** - 3**x** = 6 - 9

or, 3**x** = -3

Next, divide both sides by 3, which is the coefficent of **x**

3**x**3 = -33

**x** = -33

To simplify, divide both numerator and denominator by 3, which is the GCF of 3 and 3:

**x** = -11 or, **x** = -1